AZAS-AZAS HUKUM ISLAM - Muzakir Muzakir (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2013)
The main sources of Islamic law are the Qur'an and the Hadith. Mergingthe two gave birth to three sources, namely Consensus. Application of Islamic lawshould provide a sense of comfort for mukallaf. These conditions need to becreated so that the objectives of Islamic law to achieve happiness of the world andthe hereafter is reached. Therefore, the application should require the principles asa foundation. Principles themselves can be obtained at the legal source. The use oflegal principles is absolutely necessary for their implementation. This is veryimportant, because it will give comfort to arbitrate.